2023
DOI: 10.3390/membranes13010097
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Lipid Membrane as Memcapacitance: Capacitance–Voltage Pinched Hysteresis and Negative Insertion Conductance

Abstract: Inelastic (dissipative) effects of different natures in lipid bilayer membranes can lead to hysteresis phenomena. Early, it was shown that lipid bilayer membranes, under the action of a periodic sinusoidal voltage, demonstrate pinched-hysteresis loops in the experimental capacitance–voltage dependences and are almost the only example of the physical implementation of memcapacitance. Here, we propose an equivalent circuit and mathematical framework for analyzing the dynamic nonlinear current response of a lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The measurement method of the surface potential exploits the nonmonotonic voltage dependence of membrane capacitance [ 28 , 29 , 30 ]. In [ 29 ], it was shown that the voltage corresponding to the minimum of the capacitance current could be uniquely calculated using current responses to upward and downward half-periods of the triangular voltage. With an asymmetric addition of cyt c, the resulting difference in the surface potentials can be compensated for by an external command voltage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement method of the surface potential exploits the nonmonotonic voltage dependence of membrane capacitance [ 28 , 29 , 30 ]. In [ 29 ], it was shown that the voltage corresponding to the minimum of the capacitance current could be uniquely calculated using current responses to upward and downward half-periods of the triangular voltage. With an asymmetric addition of cyt c, the resulting difference in the surface potentials can be compensated for by an external command voltage.…”
Section: Methodsmentioning
confidence: 99%
“…A triangular alternating command voltage with amplitudes in the range of 100–200 mV and frequencies from 0.5 to 1 Hz was applied to the membrane and cyclic current-voltage characteristics were registered ( Figure 1 a). The half-difference of the current responses to upward and downward half-periods of the triangular voltage ( Figure 1 b) is proportional (if transitional processes are excluded) to the membrane capacitance [ 29 ]. To assess the difference in surface potentials for each concentration of cyt c and each pH, the voltage corresponding to the minimum half-difference of the current responses was recorded and compared with the corresponding data of the control membranes.…”
Section: Methodsmentioning
confidence: 99%